'Knowing we have these rights does not always mean we feel free to use them': athletes' perceptions of their human rights in sport. Issue 3 (16th August 2022) - Tuakli-Wosornu, Yetsa A; Goutos, Demetri; Ramia, Ioana; Galea, Natalie G; Mountjoy, Margo Lynn; Grimm, Katharina; Wu, Yinfei; Bekker, Sheree
Abstract : Objectives: Modern sport safeguarding strategies include published global rights declarations that enshrine athletes' entitlements at the policy level. It is unclear how these documents translate to athletes' lived experiences. The study aimed to determine athletes' knowledge, attitudes and beliefs about their human rights in sports settings. Setting: Web-based survey. Participants: 1159 athletes from 70 countries completed a validated web-based survey. Over half of participants (60.1%) were between 18 and 29 years, currently competing (67.1%), not members of players' unions (54.6%), elite (60.0%) and participating in individual (55.8%) non-contact (75.6%) Olympic (77.9%) sports. Gender distribution was equal. Primary and secondary outcome measures: Participant demographics (eg, gender, age) and athletes' knowledge, attitudes and beliefs about their human rights in sports settings. Results: Most (78.5%) were unaware of any athletes' rights declarations. Gender influenced participants' confidence in acting on their rights in sport significantly. Males were more likely to accept pressure from coaches and teammates than females, but age affected how likely males were to accept this pressure. Paralympic athletes were less likely to agree that violence is acceptable in sports, compared with Olympic. Player union membership increased confidence in freely expressing one's opinion in sports settings. Athletes' rights-related awareness, knowledge and beliefs were disconnected. Conclusions: Awareness raising is not enough to prevent human rights violations in sports. The cultural climate of the entire ecosystem must be targeted, using systems-level strategies to shift stakeholders' biases, beliefs and behaviours. This approach takes the onus of addressing abuse off athletes' shoulders and places accountability on sports organisations.